Nonlinear Dynamics in Coevolution of Economic and Environmental Systems - Caravaggio, Andrea; Sodini, Mauro (Frontiers in Applied Mathematics and Statistics, 2018)
The goal of this paper is to review some of the works on the dynamics of economic models in which the environmental variable is introduced. In particular, we will focus on models that in addition to giving some analytical insights into the coevolution of economic and environmental systems, they can give rise to nonlinear dynamic effects as the emergence of chaotic dynamics, multistability and (local and global) indeterminacy. However, several questions on this issue remain open and we hope that our paper may attract researchers to contribute to this topic.